Grace in Saiva Siddhanta Vedanta, Islam and Christianity - Emmanuel Pazhepura (Journal of Dharma)
The Seminar held at Tamil Nadu Theological Seminary, .Arasaradi, Madurai, in October 1971 concentrated. on the Study of "Grace" in various Religions. Specialists in various religions came together, shared their views, discussed many aspects of grace and arrived at a comprehensive concept of "Grace as viewed by Saiva Siddhiinta, Vedanta, Islam and Christianity." It is to the credit of Dr. Albrecht Frenz, that the proceedings of the seminar have been made available to us. That grace has been operating throughout the seminar becomes abundantly clear when one reads this book. I